2001
DOI: 10.1207/s15327914nc41-1&2_26
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Is Involved in the Increase of Cytochrome P-450 2B1 Expression by α-Tocopheryl Succinate in Primary Rat Hepatocytes in the Presence of Phenobarbital

Abstract: The modulation of cytochrome P-450 2B1 expression by alpha-tocopheryl succinate and whether prostaglandin E2 is involved in this modulation in primary rat hepatocytes in the presence of phenobarbital were investigated. A primary rat hepatocyte culture model that faithfully reproduces the phenobarbital response observed in vivo was used. Intracellular alpha-tocopherol content was dose dependently increased by alpha-tocopheryl succinate incubation. Hepatocytes were demonstrated to have prostaglandin E2-synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Cyclooxygenase, which is also known as PG synthase, is the key enzyme for PG synthesis. Prostaglandin E 2 , one of the end products of the COX metabolic pathway, can downregulate PB-induced CYP 2B1 expression in primary rat hepatocytes [36], and this down-regulation is through the EP 2 receptor [23]. In the present study, PGE 2 levels were significantly greater in the AA-treated group than in the other groups (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Cyclooxygenase, which is also known as PG synthase, is the key enzyme for PG synthesis. Prostaglandin E 2 , one of the end products of the COX metabolic pathway, can downregulate PB-induced CYP 2B1 expression in primary rat hepatocytes [36], and this down-regulation is through the EP 2 receptor [23]. In the present study, PGE 2 levels were significantly greater in the AA-treated group than in the other groups (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, a-tocopherol modulation on the drug-metabolizing enzyme activity and expression is an alternative explanation. Recently, we demonstrated that a-tocopherol up-regulates CYP2B1 expression via prostaglandin E 2 -mediated pathways (Tsai et al 2001). Such an effect may explain in part the higher CYP protein and mRNA content in the high-FO group, which had a greater a-tocopherol level than the MO-fed groups.…”
Section: Discussionmentioning
confidence: 89%
“…The oxazaphosphorine anticancer prodrug CPA is mainly activated by a liver P450 2B-catalyzed 4-hydroxylation that yields active and cytotoxic metabolites [24]. Dietary nutrients such as vitamin E and DHA have been shown to influence PB-induced CYP 2B1 gene expression in rat primary hepatocytes [21,25]. The underlying mechanisms of this influence are changes in prostaglandin E 2 (PGE 2 ) production and alteration of transcription factor translocation, respectively.…”
Section: Introductionmentioning
confidence: 99%